Exploring the optical behaviour of a Type Iax supernova SN 2014dt. Issue 2 (14th December 2017) - Singh, Mridweeka; Misra, Kuntal; Sahu, D K; Dastidar, Raya; Gangopadhyay, Anjasha; Bose, Subhash; Srivastav, Shubham; Anupama, G C; Chakradhari, N K; Kumar, Brajesh; Kumar, Brijesh; Pandey, S B
Abstract: We present optical photometric (up to ∼410 d since B max ) and spectroscopic (up to ∼157 d since B max ) observations of a Type Iax supernova (SN) 2014dt located in M61. SN 2014dt is one of the brightest and closest ( D  ∼ 20 Mpc) discovered Type Iax SN. It best matches the light-curve evolution of SN 2005hk and reaches a peak magnitude of MB  ∼ −18.13 ± 0.04 mag with Δ m 15  ∼ 1.35 ± 0.06 mag. The early spectra of SN 2014dt are similar to other Type Iax SNe, whereas the nebular spectrum at 157 d is dominated by narrow emission features with less blending as compared to SNe 2008ge and 2012Z. The ejecta velocities are between 5000 and 1000 km s −1, which also confirms the low-energy budget of Type Iax SN 2014dt compared to normal Type Ia SNe. Using the peak bolometric luminosity of SN 2005hk, we estimate the 56 Ni mass of ∼0.14 M⊙ . The striking similarity between SN 2014dt and SN 2005hk implies that a comparable amount of 56 Ni would have been synthesized in the explosion of SN 2014dt.